Error Resilient Multipath Video Delivery on Wireless Overlay Networks - Uma Maheswari; Sudarshan TSB (Universitas Ahmad Dahlan, 2016)
Real time applications delivering multimedia data over wireless networks still pose many challenges due to high throughput and stringent delay requirements. Overlay networks with multipath transmission is the promising solution to address the above problems. But in wireless networks the maintenance of overlay networks induce additional overheads affecting the bulky and delay sensitive delivery of multimedia data. To minimize the overheads, this work introduces the Error Compensated Data Distribution Model (ECDD) that aids in reducing end to end delays and overheads arising from packet retransmissions. The ECDD adopts mTreebone algorithm to identify the unstable wireless nodes and construct overlay tree. The overlay tree is further split to support multipath transmissions. A sub packetization mechanism is adopted for multipath video data delivery in the ECDD. A forward error correction mechanism and sub-packet retransmission techniques adopted in ECDD enables to reduce the overhead and end to end delay. The simulation results presented in this paper prove that the ECDD model proposed achieves lower end to end delay and outperforms the existing models in place. Retransmission requests are minimized by about 52.27% and bit errors are reduced by about 23.93% than Sub-Packet based Multipath Load Distribution.